On-line Programming Course Registration System (OPCRS) - Al-qatan, Saleh Sulaiman (2009)
Recently, we noted that the students in the College of Arts and Sciences(CAS) in University Utara Malaysia (UUM) are going into specializations that do not require programming skills to avoid the necessity of learning programming languages as they do not have backgrounds in programming languages such as ICT students. In this proposal we propose a prototype using Java server Pages to serve as a mediator between students and the training center which is located in FTM (Computing professional Enrichment & Development Division (CoPEN) Center).The main objective of this prototype is to improve interaction between students and the Center by providing them with the latest information about the center such as; allowing the students to know if there are any new courses they could start in the near future by sending E-mails(electronic mail) from the system to inform the student about these courses. On the other hand, this system could allow the students to register and pay for these courses online which will improve and facilitate the process of registration and payment. Moreover lecturers could use this system to inform students if he is not able to attend a certain class or if he wishes to change the timetable and the lecturers will able to upload files such as PDF, document to his students Online. By using this prototype, it will increase efficient interaction between students and staff.